2015
DOI: 10.5935/1984-6835.20150144
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Characterization of Jerivá (Syagrus romanzoffiana Cham.) Fruit Pulp

Abstract: The Chemical Characterization of Jerivá (Syagrus romanzoffiana Cham.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(20 reference statements)
0
0
0
2
Order By: Relevance
“…Catechin was found in the pulp and the seeds. These results are in accordance with the literature [ 26 ], which found hydroxy benzoic acid, caffeic acid, syringic acid, coumaric acid, ferulic acid and sinapic acid in jeriva pulp.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Catechin was found in the pulp and the seeds. These results are in accordance with the literature [ 26 ], which found hydroxy benzoic acid, caffeic acid, syringic acid, coumaric acid, ferulic acid and sinapic acid in jeriva pulp.…”
Section: Resultssupporting
confidence: 93%
“…Catechin was found in the pulp and the seeds. These results are in accordance with the literature [26], which found hydroxy benzoic acid, caffeic acid, syringic acid, coumaric acid, ferulic acid and sinapic acid in jeriva pulp. Throughout the study of polyphenols in jeriva in its soluble, insoluble and esterified portions, a study in the literature [27] reported the presence of several polyphenols such as O-methyl-gallic acid, monogalloyl hexoside, protocatechuic acid, p-hydroxybenzoic acid, ferulic acid, hydroxygallic acid, p-coumaric acid and sinapic-O-glucoside.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…18,19 A concentração do ácido p-hidroxicinâmico nos AFT (55,00 µg.g -1 ) foi superior ao tomate (10 µg.g -1 ), à polpa de jerivá (21,4 µg.g -1 ) e à polpa de jussara (46 µg.g -1 ), porém é inferior ao rabanete (56 µg.g -1 ), à cenoura (69 µg.g -1 ), ao abacate (81 µg.g -1 ) e à tangerina (130 µg.g -1 ). [17][18][19][20] Comparando os resultados do ácido phidroxicinâmico para os arilos do fruto de C. fluminensis com a polpa de jerivá, descrito por Martins e colaboradores, pode-se observar que nas duas matrizes este ácido encontra-se predominantemente na forma esterificada, apresentando aumento considerável da concentração após as etapas de hidrólise. 20…”
Section: áCidos Fenólicosunclassified
“…[17][18][19][20] Comparando os resultados do ácido phidroxicinâmico para os arilos do fruto de C. fluminensis com a polpa de jerivá, descrito por Martins e colaboradores, pode-se observar que nas duas matrizes este ácido encontra-se predominantemente na forma esterificada, apresentando aumento considerável da concentração após as etapas de hidrólise. 20…”
Section: áCidos Fenólicosunclassified